‘Am I Good Enough?’: Psychological Barriers and the Intersection of Gender, Race, and Coloniality in Brazilian Students’ Pursuit of International Education - Mendes Sousa,Ana Cecilia (2025)
This thesis analyzes Brazilian students’ psychological barriers to accessing international education opportunities. Based on a mixed-methods approach, it explores how internalized feelings of inferiority, low academic confidence, and perception of not belonging are rooted in colonial legacy, at a racial and gendered intersection, more strongly perceived by marginalized groups. The study emphasizes how internalized oppression affects Brazilian students' views of themselves and their place in global education through a decolonial and intersectional lens. The findings show the need for more inclusive policies and systems to ensure Brazilian students, especially women of color, can adequately access international opportunities, a framework widely applicable to other Global South contexts.
Keywords: International Education; Academic Mobility; Brazilian Students; Decoloniality; Intersectionality; Women of Color.